Novel biomarkers of inflammation-associated immunity in cervical cancer - Zhao, Weihong; Li, Qi; Wen, Songquan; Li, Yaqin; Bai, Ying; Tian, Zhiyu (Frontiers in Oncology, 2024)
Cervical cancer (CC) is a highly malignant gynecological cancer with a direct causal link to inflammation, primarily resulting from persistent high-risk human papillomavirus (HPV) infection. Given the challenges in early detection and mid-to late-stage treatment, our research aims to identify inflammation-associated immune biomarkers in CC. We integrated two CC datasets (GSE39001 and GSE63514) in the Gene Expression Omnibus (GEO), eliminating batch effects. This analysis identified 37 differentially expressed inflammation-related genes (DEGs). Subsequently, we discussed the different levels of immune infiltration between CC cases and controls. Weighted gene coexpression network analysis (WGCNA) identified seven immunoinfiltration-related modules in CC.We identified twelve inflammation-related immune DEGs at the intersection of these findings. Further, we build protein interaction networks using the String database and screen five hub genes using the "CytoHubba": CXC chemokine ligand 8 (CXCL8), CXC chemokine ligand 10 (CXCL10), CX3C chemokine receptor 1 (CX3CR1), Fc gamma receptors 3B (FCGR3B), and SELL. The expression of these five genes in CC was determined through PCR experiments. Additionally, we assessed their diagnostic value and carried out further analyses of the association between immune cells and them, with the aim of providing new directions for the early diagnosis and middle-and latestage treatment of CC from multiple perspectives.